Criminal Law and Civil Law Accountability for the Spread of Fake News in the Digital Era - Julvina, Julvina; Hutauruk, Rufinus Hotmaulana; Sudirman, Lu (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Freedom of expression in the digital era without any restrictions indirectly triggers the spread of fake news. The freedom to spread news or broadcasts often transcends legal, cultural and religious boundaries. Therefore, fake news is used as a tool to attack honor and bring down the good name of a person or group.Purposes of the Research: This research aims to analyze criminal and civil law regulations related to the spread of fake news in the digital era in Indonesia.Methods of the Research: Through normative legal research methods, this study examines various relevant regulations, including the Criminal Code, Civil Code, and Electronic Information and Transaction Law.Results Main Findings of the Research: The results of the study show that both criminal and civil laws already have mechanisms to overcome the spread of fake news. In the criminal realm, sanctions are given to perpetrators who spread fake news with a wide impact, such as inciting riots or violating human rights. Related articles in the Criminal Code and the Electronic Information and Transaction Law, such as Article 160 of the Criminal Code and Article 28 paragraph (3) jo. Article 45A paragraph (3) of the Electronic Information and Transaction Law, provides a strong legal basis. Meanwhile, civil law allows aggrieved individuals to claim compensation through the concept of unlawful acts in the Civil Code. A comparison between criminal and civil law shows that these two systems are complementary: criminal law focuses on providing a deterrent effect and protecting the public interest, while civil law places more emphasis on the recovery of individual losses. While existing regulations are adequate to deal with the spread of fake news, increased legal awareness in the community, stronger law enforcement, and more effective prevention mechanisms are needed to deal with the challenges in this digital age.